Zinc-elicited stress tolerance in fungi (Research, Society and Development, 2023)
Fungi for industrial and agricultural uses must endure a variety of physical and chemical challenges, collectively referred to as stresses. The fungal response to stress conditions may be due to impaired growth and metabolism. Understanding the physiology of stress responses can help alleviate the detrimental effects when the fungus is applied agricultural and industrial uses. The present study aims to review the physiological and morphological effects of zinc ions on fungi. Zinc is essential for the activity of zinc metalloenzymes, such as alcohol dehydrogenase and aldehyde dehydrogenase. It can activate riboflavin synthesis and increase protein content in fermenting yeast. However, excess zinc is toxic to the cell, and the cellular level must be finely controlled within an adequate range between 0.1 and 0.5 mM. In conclusion, a relationship between zinc and yeasts is observed but has not yet been fully defined in the fermentation process. Thus, studies are still needed to evaluate the physiological and morphological effects of zinc ions in fungi used in agriculture, such as tolerance of conidia produced in culture media with zinc or to conditions of oxidative stress, osmotic stress, ultraviolet radiation, and heat.